Lysine acetylation stabilizes SP2 protein in the silkworm Bombyx mori. (August 2016) - Zhou, Yong; Wu, Chengcheng; Sheng, Qing; Jiang, Caiying; Chen, Qin; Lv, Zhengbing; Yao, Juming; Nie, Zuoming
Graphical abstract: Highlights: The storage proteins in hemolymph were highly acetylated, especially SP2. Lysine acetylation can improve the ability of anti -apoptosis for SP2. Lysine acetylation could improve the SP2 protein level. The crosstalk between Kac and KUb could influence nutrient storage and utilization. Abstract: Lysine acetylation (Kac) is a vital post-translational modification that plays an important role in many cellular processes in organisms. In the present study, the nutrient storage proteins in hemolymph were first found to be highly acetylated—particularly SP2 protein, which contains 20 potential Kac sites. Further results confirmed that lysine acetylation could stabilize and up-regulate the protein level of anti -apoptosis protein SP2, thereby improving the survival of H2 O2 -treated BmN cells and suppressing the apoptosis induced by H2 O2 . The potential mechanism involved in the inhibition of ubiquitin-mediated proteasomal degradation by crosstalk between lysine acetylation and ubiquitination. Our results showed that the increase in the acetylation level by TSA could decrease the ubiquitination and improve the protein level of SP2, indicating that lysine acetylation could influence the SP2 protein level through competition between ubiquitination and the suppression of ubiquitin-mediated proteasomal degradation, thereby stabilizing the protein. SP2 is a major nutrient storage protein from hemolymph for amino acid storage and utilization. The crosstalk between lysine acetylation and ubiquitination of SP2 might imply an important role of lysine acetylation for nutrient storage and utilization in silkworm.